Land set up systems and beyond: Influence of soil management on water and soil conservation sewed up to a variety of pedoclimatic environments and farming systems - Altobelli, Filiberto; Napoli, Marco; Benedetti, Anna; Vargas, Ronald; Corti, Giuseppe (Italian Journal of Agronomy, 2020)
According to European Landscape Convention, the term Landscape means an area whose character is the result of the action and interaction of natural and human factors. The equilibrium between these forces is mandatory to preserve this heritage implementing a good land protection and conservation policy that implies many professional figures like agronomists and soil scientists. Italian territory includes different physiographic regions in which many human activities, especially agriculture, differently operated through the time...